Scaling clean cookstoves in displacement contexts: Reasons for limited success - Singh, Radhika (2025)
In displacement settings, something as ordinary as cooking is an extraordinarily complicated matter. Refugees often rely on firewood or charcoal, exposing them to health risks, environmental degradation, and even violence. For these reasons, increasing the adoption of “clean” cookstoves among displaced populations has long been a goal of the humanitarian sector. Clean cookstoves run on environmentally and climate friendly sources of fuel such as solar, LPG, or electricity, while traditional cookstoves use firewood or charcoal.